A Taxonomy for Psycho-Oncological Intervention Techniques in an Acute Care Hospital in Germany - Madl, Martina; Lieb, Marietta; Schieber, Katharina; Hepp, Tobias; Erim, Yesim (Oncology Research and Treatment, 2021)
Background: Due to the establishment of a nationwide certification system for cancer centers in Germany, the availability of psycho-oncological services for cancer patients has increased substantially. However, little is known about the specific intervention techniques that are applied during sessions in an acute care hospital, since a standardized taxonomy is lacking. With this study, we aimed at the investigation of psycho-oncological intervention techniques and the development of a comprehensive and structured taxonomy thereof. Methods: In a stepwise procedure, a team of psycho-oncologists generated a data pool of interventions and definitions that were tested in clinical practice during a pilot phase. After an adaptation of intervention techniques, interrater reliability (IRR) was attained by rating 10 previously recorded psycho-oncological sessions. A classification of interventions into superordinate categories was performed, supported by cluster analysis. Results: Between April and June 2017, 980 psycho-oncological sessions took place. The experts agreed on a total number of 22 intervention techniques. An IRR of 89% for 2 independent psycho-oncological raters was reached. The 22 techniques were classified into 5 superordinate categories. Discussion/Conclusion: We developed a comprehensive and structured taxonomy of psycho-oncological intervention techniques in an acute care hospital that provides a standardized basis for systematic research and applied care. We expect our work to be continuously subjected to further development: future research should evaluate and expand our taxonomy to other contexts and care settings.
CRIS-Team WoS Importer:2021-07-30

Classification of body dysmorphic disorder - What is the advantage of the new DSM-5 criteria? - Schieber, Katharina; Kollei, Ines; De Zwaan, Martina; Martin, Alexandra (Journal of psychosomatic research, 2015)
In DSM-5 the diagnosis of body dysmorphic disorder (BDD) has been subjected to two important changes: Firstly, BDD has been assigned to the category of obsessive-compulsive and related disorders. Secondly, a new criterion has been defined requiring the presence of repetitive behaviors or mental acts in response to appearance concerns. The aims of this study were to report the prevalence rates of BDD based on a DSM-5 diagnosis, and to evaluate the impact of the recently introduced DSM-5 criteria for BDD by comparing the prevalence rates (DSM-5 vs.BDD-criteria (DSM-IV/DSM-5), dysmorphic concerns, and depressive symptoms, were assessed in a representative sample of the German general population (N=2129, aged 18-65years).The association between BDD case identification based on DSM-IV and DSM-5 was strong (Phi=.95, p<.001), although point prevalence of BDD according to DSM-5 was slightly lower (2.9%, n=62 vs. 3.2%, n=68). Approximately one third of the identified BDD (DSM-5) cases reported time-consuming behavioral acts in response to appearance concerns. In detail, 0.8% of the German general population fulfilled the BDD criteria and reported repetitive acts of at least one hour/day.The revised criteria of BDD in DSM-5 do not seem to have an impact on prevalence rates. However, the recently added B-criterion reflects more precisely the clinical symptoms of BDD, and may be useful for distinguishing between various severity levels related to repetitive behaviors/mental acts.
EVALuna2:24017

Explicit and implicit approach vs. avoidance tendencies towards high vs. low calorie food cues in patients with anorexia nervosa and healthy controls - Paslakis, Georgios; Kuehn, Simone; Schaubschläger, Anke; Schieber, Katharina; Roeder, Kathrin; Rauh, Elisabeth; Erim, Yesim (Appetite, 2016)
EVALuna2:24036

Feasibility and Acceptability of an Alcohol Addiction Therapy Integrated in a Transplant Center for Patients Awaiting Liver Transplantation - Erim, Yesim; Boettcher, Michael; Schieber, Katharina; Lindner, Marion; Klein, Christian; Paul, Andreas; Beckebaum, Susanne; Mayr, Andreas; Helander, Anders (Alcohol and Alcoholism, 2016)
EVALuna2:5486

Long-term positive and negative psychosocial outcomes in young childhood cancer survivors, type 1 diabetics and their healthy peers - Kremer, Anna-Lena; Schieber, Katharina; Metzler, Markus; Schuster, Sonja; Erim, Yesim (International Journal of Adolescent Medicine and Health, 2016)
EVALuna2:18942

Mobile Technology Affinity in Renal Transplant Recipients - Reber, Sandra Therese; Scheel, J.; Stößel, Lisa; Schieber, Katharina; Jank, S.; Luker, C.; Vitinius, F.; Grundmann, F.; Eckardt, Kai-Uwe; Prokosch, Hans-Ulrich; Erim, Yesim (Transplantation Proceedings, 2018)
Medication nonadherence is a common problem in renal transplant recipients (RTRs). Mobile health approaches to improve medication adherence are a current trend, and several medication adherence apps are available. However, it is unknown whether RTRs use these technologies and to what extent. In the present study, the mobile technology affinity of RTRs was analyzed. We hypothesized significant age differences in mobile technology affinity and that mobile technology affinity is associated with better cognitive functioning as well as higher educational level.A total of 109 RTRs (63% male) participated in the cross-sectional study, with an overall mean age of 51.8 ± 14.2 years. The study included the Technology Experience Questionnaire (TEQ) for the assessment of mobile technology affinity, a cognitive test battery, and sociodemographic data.Overall, 57.4% of the patients used a smartphone or tablet and almost 45% used apps. The TEQ sum score was 20.9 in a possible range from 6 (no affinity to technology) to 30 (very high affinity). Younger patients had significantly higher scores in mobile technology affinity. The only significant gender difference was found in having fun with using electronic devices: Men enjoyed technology more than women did. Mobile technology affinity was positively associated with cognitive functioning and educational level.Young adult patients might profit most from mobile health approaches. Furthermore, high educational level and normal cognitive functioning promote mobile technology affinity. This should be kept in mind when designing mobile technology health (mHealth) interventions for RTRs. For beneficial mHealth interventions, further research on potential barriers and desired technologic features is necessary to adapt apps to patients' needs.
EVALuna:35443

Patient related factors influencing the utilization of the psycho-oncology service - Schieber, Katharina; Madl, Martina; Paslakis, Georgios; Erim, Yesim (2018)
EVALuna2:214432

Patient's Experience with Living Donation: A Questionnaire-Based Survey of 144 Living Kidney Donors - Schieber, Katharina; Gaag, Sonja; Heller, Katharina; Erim, Yesim (Psychotherapie Psychosomatik Medizinische Psychologie, 2018)
Keywords: evaluation; consequences; psychosocial consequences; living donation; living kidney donation

Psychological processing of a kidney transplantation, perceived quality of life, and immunosuppressant medication adherence - Scheel, Jennifer Felicia; Schieber, Katharina; Reber, Sandra Therese; Jank, Sabine; Eckardt, Kai-Uwe; Grundmann, Franziska; Vitinius, Frank; De Zwaan, Martina; Bertram, Anna; Erim, Yesim (Patient Preference and Adherence, 2019)
Introduction: Though psychosocial well-being and quality of life generally improve after transplantation, a relevant proportion of patients suffers from psychosocial problems. Further analysis of the psychological coping after kidney transplantation is needed to identify patients at risk. The aim of this study was to examine the psychological response after kidney transplantation and its associations with health-related quality of life and immunosuppressant medication adherence.
CRIS-Team WoS Importer:2019-06-04

Psychosocial distress and utilization of professional psychological care in cancer patients: An observational study in National Comprehensive Cancer Centers (CCCs) in Germany. - Weis, Joachim; Hoenig, Klaus; Bergelt, Corinna; Faller, Hermann H.; Brechtel, Anette; Hornemann, Beate; Stein, Barbara; Teufel, Martin; Goerling, Ute; Erim, Yesim; Geiser, Franziska; Niecke, Alexander; et al. (Psycho-Oncology, 2018)

Psychosocial Variables Associated with Immunosuppressive Medication Non-Adherence after Renal Transplantation. - Scheel, Jennifer Felicia; Schieber, Katharina; Reber, Sandra; Stoessel, Lisa; Waldmann, Elisabeth; Jank, Sabine; Eckardt, Kai-Uwe; Grundmann, Franziska; Vitinius, Frank; de Zwaan, Martina; Bertram, Anna; Erim, Yesim (Frontiers in Psychiatry, 2018)

Return to work after cancer: Improved mental health in working cancer survivors - Lieb, Marietta; Wuensch, Alexander; Schieber, Katharina; Bergelt, Corinna; Faller, Hermann; Geiser, Franziska; Goerling, Ute; Hoenig, Klaus; Hornemann, Beate; Maatouk, Imad; Niecke, Alexander; Stein, Barbara; et al. (Psycho-Oncology, 2022)
Objective Aim of the study was to compare working and non-working patients over a period of 12 months regarding socio-demographic, cancer-specific and mental health parameters. Methods This study was conducted as part of a Germany-wide longitudinal survey among 1398 patients in 13 national Comprehensive Cancer Centers. The sample used for analysis consisted of n = 430 cancer patients younger than 65 years (age M = 52.4 years, SD = 8.1; 67.0% females). Socio-demographic, cancer-specific and mental health parameters (Depression: Patient Health Questionnaire, Anxiety: Generalized Anxiety Disorder Scale, Distress: Distress Thermometer) were assessed at baseline during hospitalization and at 12 months follow-up. Results 73.7% of all patients (n = 317) have returned to work after one year. While working and non-working patients did not differ in socio-demographic parameters, there were significant differences in the presence of metastases, tumor and treatment status. Mixed analysis of variances revealed significant interactions between working status and time for depression (p = 0.009), anxiety (p = 0.003) and distress (p = 0.007). Non-working patients reported higher levels of depression, anxiety and distress than working patients over time. A logistic regression showed significant associations between lower depression (p = 0.019), lower distress (p = 0.033) and the absence of a tumor (p = 0.015) with working status. Conclusions The majority of cancer survivors returned to work. Non-working patients had higher levels of depression, anxiety and distress than working patients. After controlling for cancer-specific factors, mental health parameters were still independently associated with working status. Return to work can thus be associated with an improved mental health in cancer survivors. In order to establish causality, further research is necessary.
CRIS-Team WoS Importer:2022-01-21

Self-reports on symptoms of alcohol abuse: liver transplant patients versus rehabilitation therapy patients - Schieber, Katharina; Lindner, Marion; Sowa, Jan-Peter; Gerken, Guido; Scherbaum, Norbert; Kahraman, Alisan; Canbay, Ali; Erim, Yesim (Progress in Transplantation, 2015)
EVALuna2:24026

The course of cancer-related insomnia: don't expect it to disappear after cancer treatment - Schieber, Katharina; Niecke, Alexander; Geiser, Franziska; Erim, Yesim; Bergelt, Corinna; Büttner-Teleaga, Antje; Maatouk, Imad; Stein, Barbara; Teufel, Martin; Wickert, Martin; Wuensch, Alexander; Weis, Joachim (Sleep Medicine, 2019)
Objective: The study aimed to examine the 12-month course of cancer-related insomnia (CRI) and to identify possible predictors for the prevalence and persistence of CRI. Methods: This longitudinal multicenter study included N = 405 patients with cancer (56% females, mean age: 58.6 years). CRI was measured by the Insomnia Severity Index (ISI). Socio-demographic and clinical data, as well as psychological parameters (Distress Thermometer, PHQ-9, GAD-7, and EORTC-Fatigue), were assessed at baseline (T1) and 12 months later (T2). Results: In our sample, a high prevalence of relevant insomnia symptoms (49.4%, ISI > 7) was found, while a clinical insomnia diagnosis was verified in 12.8% (ISI > 14). When insomnia was present at T1, this problem was persistent after one year in 64%. At T2, however, significantly more women suffered from insomnia symptoms (53.3% women vs. 39.3% men; p = 0.003). Insomnia was associated with many clinical and psychological parameters, especially with fatigue (r = 0.5). Multiple regression analysis revealed that, in women, only insomnia at T1 was a significant predictor for insomnia at T2 (R2 = 0.40; F(5) = 12.5; p < 0.001), whereas in men insomnia, depressive symptoms and the use of psychotropic drugs at T1 predicted the extent of insomnia at T2 (R2 = 0.28; F(7) = 9.5; p < 0.001). In all participants, levels of distress, depression, and anxiety decreased from T1 to T2 (p's < 0.016). Conclusion: Insomnia is a common disorder in cancer patients. Although medical and psychological parameters improved during the 12-month course of cancer treatment, our results show that insomnia is highly persistent, especially in women. This indicates that adequate support for those affected is needed. Clinical Trial Registration Number: DRKS00004860.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Cancer; Gender-specific predictors; Insomnia; Prevalence; Psychological distress; Sleep disorder

The Dysmorphic Concern Questionnaire in the German General Population: Psychometric Properties and Normative Data - Schieber, Katharina; Kollei, Ines; Zwaan, Martina De; Martin, Alexandra (Aesthetic Plastic Surgery, 2018)
BACKGROUND: The Dysmorphic Concern Questionnaire (DCQ) is a widely used screening instrument assessing dysmorphic concerns ranging from a mild to an excessive level. It is often used in the setting of plastic and aesthetic surgery. The present study aimed at examining the psychometric properties of the DCQ in a random general population sample. METHODS: A representative sample of the German general population (N = 2053, aged between 18 and 65 years, 54% females) completed the DCQ as well as questionnaires on depression and appearance concerns. RESULTS: The DCQ showed a good internal consistency with Cronbach's α = 0.81. Its one-factor model structure was confirmed. Normative data were stratified according to gender and age. Women reported more dysmorphic concerns than men, but also within females the DCQ scores differed between age classes. Overall, 4.0% of the sample reported excessive dysmorphic concerns based on a previously defined cutoff sum score ≥ 11. CONCLUSION: The DCQ is a valid and reliable screening tool to identify individuals with excessive dysmorphic concerns. Excessive concerns may indicate also the presence of body dysmorphic disorder, but for verifying a final diagnosis the use of a structured clinical interview is necessary. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these evidence-based medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
EVALuna2:214444

The influence of patient-related factors on the frequency and duration of psycho-oncological sessions in a university cancer center - Madl, Martina; Lieb, Marietta; Schieber, Katharina; Erim, Yesim (Journal of Psychosocial Oncology, 2021)
Objective The present study aimed at identifying factors that are associated with the frequency and duration of psycho-oncological sessions. Design In a retrospective single-center study, data of all patients who made use of the psycho-oncological service (POS) at the University Hospital Erlangen from April 2017 - March 2018 were registered. Sample Over the course of one year, N = 1601 patients made use of the POS. Methods In the hospital's digital documentation system, relevant data such as frequency of sessions, duration of sessions, gender, age, family status, preexisting mental disorder, prior psychotherapy, cancer entity (type of cancer) and treatment modality were recorded. Socio-demographic and clinical parameters were analyzed to predict frequency and duration of the psycho-oncology sessions. Findings Regression analyses revealed that among POS users, women, younger patients, patients with a longer hospital stay and those with a preexisting mental disorder attended significantly more sessions than other patients (p < .001). Patients with skin cancer had significantly fewer POS sessions than those with a hematological diagnosis. Also, patients who had undergone surgery had significantly fewer sessions than patients with pharmacological treatment. Younger age and a longer hospital stay significantly predicted longer sessions (p < .001). In the regression model, patients with brain tumors and lung cancer had significantly longer sessions than patients with skin cancer. Implications With the identification of specific risk groups that require more and longer sessions, we can provide the basis for more patient-tailored intervention approaches and better scheduling according to the patients' needs. However, our results also suggest that the frequency and duration of POS sessions also depend on illness- and treatment-related criteria, e.g. the length of the hospital stay.
CRIS-Team WoS Importer:2021-12-10

The influence of the setting on alcohol self-reports: a comparison of the setting of liver transplantation and rehabilitation therapy - Schieber, Katharina; Lindner, M.; Sowa, J. P.; Gerken, G.; Scherbaum, N.; Kahraman, A.; Canbay, A.; Erim, Yesim (Transplant International, 2014)

Up to a Third of Renal Transplant Recipients Have Deficiencies in Cognitive Functioning - Stößel, Lisa; Schieber, Katharina; Jank, Sabine; Reber, Sandra Therese; Grundmann, Franziska; Lüker, Christine; Vitinius, Frank; Paslakis, Georgios; Eckardt, Kai-Uwe; Erim, Yesim (Progress in Transplantation, 2017)